Investigation of Fluid-driven Carbonation of a Hydrated, Forearc Mantle Wedge using Serpentinite Cores in High-pressure Experiments. (27th February 2020) - Sieber, Melanie J; Yaxley, Gregory M; Hermann, Jörg
Abstract: High-pressure experiments were performed to investigate the effectiveness, rate and mechanism of carbonation of serpentinites by a carbon-saturated COH fluid at 1·5–2·5 GPa and 375–700 °C. This allows a better understanding of the fate and redistribution of slab-derived carbonic fluids when they react with the partially hydrated mantle within and above the subducting slab under pressure and temperature conditions corresponding to the forearc mantle. Interactions between carbon-saturated CO2 –H2 O–CH4 fluids and serpentinite were investigated using natural serpentinite cylinders with natural grain sizes and shapes in piston-cylinder experiments. The volatile composition of post-run fluids was quantified by gas chromatography. Solid phases were examined by Raman spectroscopy, electron microscopy and laser ablation inductively coupled plasma mass spectrometry. Textures, porosity and phase abundances of recovered rock cores were visualized and quantified by three-dimensional, high-resolution computed tomography. We find that carbonation of serpentinites is efficient at sequestering CO2 from the interacting fluid into newly formed magnesite. Time-series experiments demonstrate that carbonation is completed within ∼96 h at 2 GPa and 600 °C. With decreasing CO2, aq antigorite is replaced first by magnesite + quartz followed by magnesite + talc + chlorite in distinct, metasomatic fronts. Above antigorite stability magnesite + enstatite + talc + chlorite occur additionally. The formation of fluid-permeable reaction zones enhances the reaction rate and efficiency of carbonation. Carbonation probably occurs via an interface-coupled replacement process, whereby interconnected porosity is present within reaction zones after the experiment. Consequently, carbonation of serpentinites is self-promoting and efficient even if fluid flow is channelized into veins. We conclude that significant amounts of carbonates may accumulate, over time, in the hydrated forearc mantle.